ANALISIS PENGARUH KOMPETENSI TERHADAP PERAN-PERAN BARU PROFESIONAL SUMBER DAYA MANUSIA - Suryaningtyas, Dianawati (Jurnal Ekonomi Modernisasi, 2013)
The fast changes and complexity of busines environment in global situation has forced many companies to make transformation in organization for gaining sustainable competitive advantage. Facing this new challenge, many of them have made human resource transformation. High standard quality of competencies of human resource professionals are needed to perform their roles excellently, in order to be succeeded in implementing human resource transformation . This survey research identifies and describes competencies of human resource professionals and the current execution of their roles. It also examines the significant influence of those competencies on roles of human resource professionals within human resource transformation. Respondents are Human Resource Manager or similar position in human resource or the person in charge in human resource. Convenience sampling is used to obtain samples in the communities of Human Resource Managers in Sidoarjo dan Pasuruan. Referring to complexity of the research framework and amount of samples, partial least square is used to analyse data. This research analyses the significant influence of HR Competencies on HR Roles. The result shows that HR Competencies on HR Professional Competencies have the most significant influence on HR Roles on Operational Focus. In conclusion, the respondents’ position is still on traditional human resource function and work more on day-to-day activities (operational). It reveals that human resource transformation is not done in their companies yet. Implication to repondents is that they need human resource consultant to help them implement human resource transformation because they are still lack of competencies and roles.